Does the CO2 laser reduce bond strength in different types of ceramic brackets? - Fábio Lourenço Romano; Giovanna Pessoti; Rodrigo Galo; Jaciara Miranda Gomes-Silva; Marília Pacífico Lucisano; Maria Cristina Borsatto; Paulo Nelson-Filho
ABSTRACT OBJECTIVE: The aim of this study was to assess in vitro the influence of the CO2 laser and of the type of ceramic bracket on the shear bond strength (SBS) to enamel. METHODS: A total of 60 enamel test surfaces were obtained from bovine incisors and randomly assigned to two groups, according to the ceramic bracket used: Allure (A); Transcend (T). Each group was divided into 2 subgroups (n = 15): L, laser (10W, 3s); C, no laser, or control. Twenty-four hours after the bonding protocol using Transbond XT, SBS was tested at a crosshead speed of 0.5 mm/min in a universal testing machine. After debonding, the Adhesive Remnant Index (ARI) was evaluated at 10 x magnification and compared among the groups. Data were analyzed by one-way ANOVA, Tukey's, Mann-Whitney's and Kruskal-Wallis tests (α = 0.05). RESULTS: Mean SBS in MPa were: AL = 0.88 ± 0.84; AC = 12.22 ± 3.45; TL = 12.10 ± 5.11; TC = 17.71 ± 6.16. ARI analysis showed that 73% of the specimens presented the entire adhesive remaining on the tooth surfaces (score 3). TC group presented significantly higher SBS than the other groups. The lased specimens showed significantly lower bond strength than the non-lased groups for both tested brackets. CONCLUSION: CO2 laser irradiation decreased SBS values of the polycrystalline ceramic brackets, mainly Allure.